Efficacy and safety of adrenocorticotropic hormone gel in refractory dermatomyositis and polymyositis. Issue 5 (13th December 2017) - Aggarwal, Rohit; Marder, Galina; Koontz, Diane Carol; Nandkumar, Preeya; Qi, Zengbiao; Oddis, Chester V
Abstract : Aim: To evaluate the efficacy, safety, tolerability and steroid-sparing effect of repository corticotropin injection (RCI), in an open-label clinical trial, in refractory adult polymyositis (PM) and dermatomyositis (DM). Methods: Adults with refractory PM and DM were enrolled by two centres. Inclusion criteria included refractory disease defined as failing glucocorticoid and/or ≥1 immunosuppressive agent, as well as active disease defined as significant muscle weakness and >2 additional abnormal core set measures (CSMs) or a cutaneous 10 cm Visual Analogue Scale score of ≥3 cm and at least three other abnormal CSMs. All patients received RCI of 80 units subcutaneously twice weekly for 24 weeks. The primary end point for the trial was the International Myositis Assessment and Clinical Studies definition of improvement. Secondary end points included safety, tolerability, steroid-sparing as well as the 2016 American College of Rheumatology (ACR)/European League Against Rheumatism myositis response criteria (EULAR) Results: Ten of the 11 enrolled subjects (6 DM, 4 PM) completed the study. Seven of 10 met the primary end point of efficacy at a median of 8 weeks. There was a significant decrease in prednisone dose from baseline to conclusion (18.5 (15.7) vs 2.3 (3.2); P<0.01). Most individual CSMs improved at week 24 compared with the baseline, with the muscle strength improving by >10% and the physician global by >40%. RCI was considered safe and tolerable. No patient developed significant weight gain or an increase of haemoglobin A1c or cushingoid features. Conclusion: Treatment with RCI was effective in 70% of patients, safe and tolerable, and led to a steroid dose reduction in patients with adult myositis refractory to glucocorticoid and traditional immunosuppressive drugs. Trial registration number: NCT01906372 ; Results.